An Empirical Analysis of Financial Performance and Solvency Position of Selected Public Sector Banks with Parametric Statistical Techniques - Paul, Sanjib; Bhattacharyya, Sandip (International Journal of Engineering and Management Research, 2026)
At the present time, people are closely connected with many financial activities in their daily lives. Our financial system has different sectors that help individuals and businesses meet their financial needs. in a competitive scenario the banking sector plays a major and very important role in the economy. financial system includes Banks to collect deposits, provide loans, and support economic growth. In addition to in recent years, many banks have been facing serious problems related to their solvency position. Our study focuses on a comparison of the solvency position of two major banks: Punjab National Bank (PNB), which is a public sector bank, and Axis Bank, which is a private sector bank. The main objective our paper is to examine and compare the financial strength by using financial statement analysis from their annual report. In our research paper several key financial ratios such as the NPA ratio and the Capital Adequacy Ratio (CAR) have been calculated. it help in understanding the ability of banks to meet their long-term obligations and manage financial risks. We also used the modified Altman’s Z-score model to get an overall view of the financial health of both banks. To check the statistical significance of the results, we applied a single-factor ANOVA test on the Z-score and selected financial ratios. This helped us to identify whether there is any significant difference in the solvency position of the two banks.